Multi-configuration electron-nuclear dynamics: an open-shell approach - Wang, Cong; Ulusoy, Inga; Aebersold, Lucas E.; Wilson, Angela K. (The journal of chemical physics, 2021)
The multi-configuration electron-nuclear dynamics for open shell systems with a spin-unrestricted formalism is described. The mean fields are evaluated using second-order reduced density matrices for electronic and nuclear degrees of freedom. Applications to light-element diatomics including equilibrium geometries, electronic energies, dipole moments, and absorption spectra are presented. The von Neumann entropies for different spin states of a LiH molecule are compared.
Gesehen am 26.11.2021